2021
DOI: 10.1186/s12957-021-02342-y
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis of m5C regulator genes reveals consistent epigenetic landscape changes in multiple cancers

Abstract: Background 5-Methylcytosine (m5C) is a reversible modification to both DNA and various cellular RNAs. However, its roles in developing human cancers are poorly understood, including the effects of mutant m5C regulators and the outcomes of modified nucleobases in RNAs. Methods Based on The Cancer Genome Atlas (TCGA) database, we uncovered that mutations and copy number variations (CNVs) of m5C regulatory genes were significantly correlated across ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…The patient information was similar to that in a previous study (He et al, 2021). As shown in Figure 3, eIF4A1 was significantly overexpressed in tumor tissues compared to normal control tissues, including breast invasive carcinoma (BRCA), cholangiocarcinoma (CHOL), colon adenocarcinoma (COAD), esophageal carcinoma (ESCA), head and neck squamous cell carcinoma (HNSC), kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP), liver hepatocellular carcinoma (LIHC), lung adenocarcinoma (LUAD), lung squamous cell carcinoma (LUSC), prostate adenocarcinoma (PRAD), rectum adenocarcinoma (READ), stomach adenocarcinoma (STAD), and uterine corpus endometrial carcinoma (UCEC).…”
Section: Mrna Expression Levels Of the Eif4a Family Based On Public Database Analysismentioning
confidence: 54%
“…The patient information was similar to that in a previous study (He et al, 2021). As shown in Figure 3, eIF4A1 was significantly overexpressed in tumor tissues compared to normal control tissues, including breast invasive carcinoma (BRCA), cholangiocarcinoma (CHOL), colon adenocarcinoma (COAD), esophageal carcinoma (ESCA), head and neck squamous cell carcinoma (HNSC), kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP), liver hepatocellular carcinoma (LIHC), lung adenocarcinoma (LUAD), lung squamous cell carcinoma (LUSC), prostate adenocarcinoma (PRAD), rectum adenocarcinoma (READ), stomach adenocarcinoma (STAD), and uterine corpus endometrial carcinoma (UCEC).…”
Section: Mrna Expression Levels Of the Eif4a Family Based On Public Database Analysismentioning
confidence: 54%
“…However, this risk signature included the differential expressed genes (DEGs) as well as autophagy-related genes (ARGs) for regression analysis, and some ARGs did not reach DEGs criteria, which may contribute to the potential bias for this risk signature. Additionally, ubiquitination was considered to control multiple steps of autophagy, essential for autophagy flux regulation in a variety of signaling pathways [ 30 32 ]. DEGs related to ubiquitination may provide a superior prediction value than those related to ARGs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have also found thousands of m5C methylation peaks in circRNAs of HCC tissue, and the number and distribution of these methylation peaks are significant between HCC and adjacent tissues (He et al, 2020b). Whole chromosome level analysis showed a significantly different distribution of m5C-methylated circRNA in multiple chromosomes between cancer and adjacent tissues, especially the X chromosome, suggesting that m5C changes extensively in HCC tissues and may affect HCC phenotypes through multiple avenues (Torsin et al, 2021).…”
Section: Rna 5-methylcytosine Epigenetic Modification In Hepatocellular Carcinomamentioning
confidence: 99%
“…To date, research on m5C in HCC has made some progress, as shown in Figure 2B. Many studies have shown that the high expression of almost all m5C regulators is significantly related to the shorter overall survival period of HCC patients except for NSUN7, suggesting that the dysfunction of m5C regulators has a strong impact on HCC progression (He et al, 2021). Since then, a study used clinical information from the TCGA database to assess m5C regulator alterations and the survival rate in patients and found that the p-value of the NSUN5 and ALYREF genes in HCC is less than 0.05, as well as the significant difference in the NSUN6 gene, which provides an important basis for exploring m5C regulators as potential therapeutic targets for HCC (Song et al, 2021).…”
Section: Rna 5-methylcytosine Epigenetic Modification In Hepatocellular Carcinomamentioning
confidence: 99%